2020
DOI: 10.3389/fpsyg.2020.00431
|View full text |Cite
|
Sign up to set email alerts
|

How Schools Affect Student Well-Being: A Cross-Cultural Approach in 35 OECD Countries

Abstract: A common approach for measuring the effectiveness of an education system or a school is the estimation of the impact that school interventions have on students' academic performance. However, the latest trends aim to extend the focus beyond students' acquisition of knowledge and skills, and to consider aspects such as well-being in the academic context. For this reason, the 2015 edition of the international assessment system Programme for International Student Assessment (PISA) incorporated a new tool aimed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 56 publications
2
44
0
4
Order By: Relevance
“…PISA provides various measures in different dimensions of student well-being. Especially those related to cognitive well-being provide useful insights into differences between schools, but even in this case contribution of schools to student well-being is limited (Govorova et al, 2020). Thus, the results of this and other studies pose a question whether student well-being can be indeed shaped by education or school-level policy.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…PISA provides various measures in different dimensions of student well-being. Especially those related to cognitive well-being provide useful insights into differences between schools, but even in this case contribution of schools to student well-being is limited (Govorova et al, 2020). Thus, the results of this and other studies pose a question whether student well-being can be indeed shaped by education or school-level policy.…”
Section: Discussionmentioning
confidence: 88%
“…The purpose of our paper is to fill this gap by developing a model of student subjective well-being that separates relations at different levels and controls for a variety of personal and education-related factors. Similar approaches were applied to different aspects of student well-being and decomposition of results at the student and school level (Govorova et al, 2020). We develop a similar analysis for the subjective well-being measure, but we also add focus on between country comparisons.…”
Section: How To Measure Student Subjective Well-being?mentioning
confidence: 99%
“…it furthers extant research into student well-being and inclusion via digital technology use within the context of schools’ innovation vision and planning ( Carretero et al, 2017 ; Govorova et al, 2020 ). There is currently a lack of published research into these issues, so the work reported here presents fresh insights.…”
Section: Introductionmentioning
confidence: 75%
“…This is in line with recent empirical studies on well-being ( Lombardi et al, 2019 ) that emphasize the importance of integrating socio-emotional development in schools’ daily practice ( Burns and Gottschalk, 2019 ). Such type of school-level interventions, which have emerged to be more successful in some European countries including Italy ( Govorova et al, 2020 ), encompasses key components of well-being and inclusion through technologies such as relationships , school community , safety , individual learning needs , active learning , and collaboration , explored in the SELFIE self-reflection process ( Kampylis et al, 2016 , 2019 ). Similarly, research currently being performed in the EC ERASMUS+SHERPA project ( ErasmusPlus, 2020 ) includes the design and testing of a pedagogical innovation toolkit that complements and operationalizes schools’ SELFIE self-reflection on digital technology use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation